The Role of Banking Merger and Acquisition in Improving Operational Performance: Empirical Study on Palestinian Banks - Kannan, Feda; Rahhal, Akram; Issa, Niveen (Archives of Business Research, 2024)
This study examines the role of mergers and acquisitions (M&A) in enhancing the operational performance of banks within the Palestinian banking sector. A quantitative research methodology was employed, using simple linear regression analysis to assess the relationship between M&A activities and operational efficiency. The study sample comprised financial data from Palestinian banks involved in M&A transactions since the sector’s inception. The analysis covered a ten-year period, segmented into two intervals: five years preceding and five years following the M&A events. The results reveal a statistically significant positive correlation between M&A and improvements in key operational performance indicators (Assets Turnover, Cash Flow Margin, bank efficiency ratio, Credit to Deposit Ratio). Based on these findings, the study advocates for the consolidation of smaller banks to form larger, more competitive financial institutions capable of meeting the evolving demands of the Palestinian economy. Furthermore, the study highlights the importance of proactive regulatory support from the Palestinian Monetary Authority, including capital adequacy directives designed to incentivize M&A activity and strengthen the resilience of the banking sector.